Pharmacokinetic and in vivo studies with azithromycin (CP-62,993), a new macrolide with an extended half-life and excellent tissue distribution. - Girard, A E (1987)
Azithromycin (CP-62,993), a new acid-stable 15-membered-ring macrolide, was well absorbed following oral administration in mice, rats, dogs, and cynomolgus monkeys. This compound exhibited a uniformly long elimination half-life and was distributed exceptionally well into all tissues. This extravascular penetration of azithromycin was demonstrated by tissue/plasma area-under-the-curve ratios ranging from 13.6 to 137 compared with ratios for erythromycin of 3.1 to 11.6. The significance of these pharmacokinetic advantages of azithromycin over erythromycin was shown through efficacy in a series of animal infection models. Azithromycin was orally effective in treating middle ear infections induced in gerbils by transbulla challenges with amoxicillin-resistant Haemophilus influenzae or susceptible Streptococcus pneumoniae; erythromycin failed and cefaclor was only marginally active against the H. influenzae challenge. Azithromycin was equivalent to cefaclor and erythromycin against Streptococcus pneumoniae. In mouse models, the new macrolide was 10-fold more potent than erythromycin and four other antibiotics against an anaerobic infection produced by Fusobacterium necrophorum. Similarly, azithromycin was effective against established tissue infections induced by Salmonella enteritidis (liver and spleen) and Staphylococcus aureus (thigh muscle); erythromycin failed against both infections. The oral and subcutaneous activities of azithromycin, erythromycin, and cefaclor were similar against acute systemic infections produced by Streptococcus pneumoniae, Streptococcus pyogenes, Streptococcus viridans, or S. aureus, whereas azithromycin was more potent than erythromycin and cefaclor against the intracellular pathogen Listeria monocytogenes. The pharmacokinetic advantage of azithromycin over erythromycin in half-life was clearly demonstrated in prophylactic treatment of an acute mouse model of S. aureus infection. These properties of azithromycin strongly support the further evaluation of this new macrolide for use in community-acquired infections of skin or soft tissue and respiratory diseases.